PENGEMBANGAN LEMBAR KERJA SISWA IPA TERPADU BERBASIS TABLOID TEMA ROKOK TERHADAP HASIL BELAJAR SISWA - wilujeng, ayu; Muharrami, Laila Khamsatul; Hadi, Wiwin Puspita; Ahied, Moch (Program Studi Pendidikan IPA, Universitas Trunojoyo Madura, 2022)
The aim of this research was to know validity, and student’s response of the student worksheet based tabloid cigarette theme. The kinds of research was RnD (research and development) using Borg and Gall model but reserach is limited to 6 stages until product trial. Design of this research was one-shot case study. The reseach held in SMP Negeri 7 Bangkalan, VIII-C class, academic year 2017/2018. Development science student worksheet be measured from validity of student worksheet, readable of student worksheet, and student’s response. The average result of validity at material aspect was 87,8% with valid category, reliability 85,1% with good category, validity at media aspek was 94,1% with valid category, reliability 88,3% with good category and validity at equipment aspek was 94,4% with valid category, reliability 90,6% with good category. The average result of readable student worksheet was 55% with reability category. The average result of the student questionnaire assessment is 63% in good category. The result of individual learning outcomes was categorized as 16 students with was percentage was 76,2% and not complete as many as 5 students with a percentage was 23,8%. The average result of students response assesment was 63% with interesting category. The tabloid based integrated science student worksheet considered feasible to use.